MAQASHID AL-QUR'AN AND BUDGET EFFICIENCY - Samsul Ariyadi (PT. Jurnal Center Indonesia Publisher, 2025)
This study examines the relationship between the concept of Maqashid Al-Quran and the optimization of budget management in the context of Islamic economics. Using the systematic literature review method, this article collects and analyzes publications from Scopus indexed journals in the last 10 years to identify conceptual frameworks and indicators of budget efficiency that can be synergized with the principles of Maqashid Al-Quran. The findings of the study show that the implementation of maqashid values—such as the protection of soul, religion, intellect, descent, and property—can be the basis for formulating budgeting policies that are not only efficient but also socially just. In addition, this article develops an innovative analysis model, integrates budget efficiency indicators with the maqashid principle, and offers practical implementation recommendations for researchers and policymakers. The implications of this research are expected to help in the formulation of more holistic and progressive Islamic economic policies. This research has shown that the integration of the principles of Maqashid Al-Quran into budget management has the potential to improve fiscal policy by strengthening aspects of justice, transparency, and efficiency. Using the systematic literature review method, this article not only identifies gaps in the conventional literature, but also offers an innovative framework that can be used as a reference for researchers and practitioners in the development of Islamic economics. The implementation of this framework requires a joint commitment between stakeholders to reform fiscal governance and integrate ethical values at every policy stage. It is hoped that the results of this research will provide inspiration for the development of a long-term strategy that is progressive, based on maqashid in budget management, and will be an important contribution in realizing public governance that is fair, efficient, and oriented towards community welfare.